Dual-functional turn-on fluorescent probe for discriminative sulfite and sulfide detection via organic/aqueous ratio tuning and its application in real samples. (October 2022) - Su, Ching-Chun; Kim, Kyoung-Rok; Hong, Jong-In
Abstract: Sulfite and sulfide are substances commonly present in food, biological and industrial processes. While excess amounts of these anions can elicit physiological disorders in humans, there are only limited examples of probes capable of selectively detecting both of them. In this study, we present a sulfite/sulfide dual-functional probe 1 based on a dimethylaminonaphthalene-oxazaborine fluorophore and a dicyanovinyl reaction site. Probe 1 enabled a highly selective detection of sulfite under acetonitrile/tris buffer (85:15, v/v), discriminating sulfite from common interfering species such as sulfide, cyanide, and biothiols. The probe fully responded to sulfite within 4 min, with an 18-fold increase in the fluorescence intensity. Besides, probe 1 was also able to selectively sense sulfide in pure acetonitrile, while displaying a detection limit as low as 96 nM. Mechanistic studies revealed that a large 170 nm Stokes shift of the probe after sulfite/sulfide detection can be ascribed to the nucleophilic addition of sulfite/sulfide to the dicyanovinyl moiety, which broke the conjugation system between the fluorophore scaffold and the dicyanovinyl group, thereby triggering the intramolecular charge transfer effect. Finally, the probe displayed good capability for sensing sulfite and sulfide in real samples with good recoveries, proving its potential in the determination of sulfite and sulfide concentrations for real-life applications. Graphical abstract: Image 1 Highlights: A dual-functional fluorescent probe for sulfite and sulfide detection was synthesized. The probe displayed sulfite selectivity in acetonitrile/water mixture and sulfide selectivity in acetonitrile. Discriminative sensing was achieved by tuning the solvent ratio. The probe can detect sulfite and sulfide quantitatively in tap water and real alcoholic drink samples.